The Neurobiology of Zika Virus: New Models, New Challenges - Moura, Luciana Monteiro; Ferreira, Vinicius Leati de Rossi; Loureiro, Rafael Maffei; de Paiva, Joselisa Péres Queiroz; Rosa-Ribeiro, Rafaela; Amaro, Edson; Soares, Milena Botelho Pereira; Machado, Birajara Soares (Frontiers in Neuroscience, 2021)
The Zika virus (ZIKV) attracted attention due to one striking characteristic: the ability to cross the placental barrier and infect the fetus, possibly causing severe neurodevelopmental disruptions included in the Congenital Zika Syndrome (CZS). Few years after the epidemic, the CZS incidence has begun to decline. However, how ZIKV causes a diversity of outcomes is far from being understood. This is probably driven by a chain of complex events that relies on the interaction between ZIKV and environmental and physiological variables. In this review, we address open questions that might lead to an ill-defined diagnosis of CZS. This inaccuracy underestimates a large spectrum of apparent normocephalic cases that remain underdiagnosed, comprising several subtle brain abnormalities frequently masked by a normal head circumference. Therefore, new models using neuroimaging and artificial intelligence are needed to improve our understanding of the neurobiology of ZIKV and its true impact in neurodevelopment.